EVALUATION OF EFFICIENCY OF PARKING SYSTEM FORMATION ON EXAMPLE OF KHARKIV - Kholodova, O.; Холодова, О. О.; Холодова, О. А. (Харьковский национальный автомобильно-дорожный университет, 2015)
It is proposed to use the known dependence of the change of indicators of transport traffic functioning, namely the total travel time, depending on the nature of placing the cars parked on the road network of the city to determine the effectiveness of the system of parking. The technique tested on example of Kharkiv allowed to establish that as a result of formation of car parks in cities the total travel time of all road users of the road network is reduced.
ОЦІНКА ЕФЕКТИВНОСТІ ФОРМУВАННЯ СИСТЕМИ ПАРКІНГІВ НА ПРИКЛАДІ М. ХАРКІВ
ОЦЕНКА ЭФФЕКТИВНОСТИ ФОРМИРОВАНИЯ СИСТЕМЫ ПАРКИНГОВ НА ПРИМЕРЕ Г. ХАРЬКОВ
Keywords: central downtown; parking system; street and road network; parking network; social and economic effects; travel time; центральна ділова частина міста; система паркінгів; вулично-дорожня мережа; мережа паркування; соціальний та економічний ефект; витрати часу; центральная деловая часть города; система паркингов; улично-дорожная сеть; парковочная сеть; социальный и экономичный эффект; затраты времени; 656.13